CONTRIBUCIÓN DE LA MERCADOTECNIA EN LA UTILIZACIÓN DEL SMARTPHONE PARA VIDEOJUEGOS, CONVIRTIÉNDOLA EN UNA POSIBLE ADICCIÓN EN LOS JÓVENES - Fischer de la Vega, Laura Estela; Correa, Graciela Bribiesca; Sánchez, David Chávez (European Scientific Journal, ESJ, 2015)
Currently young people are increasing the activities they perform in their Smartphone, making it an important part in their lives; one of these activities is dedicated to video games. One exploratory research was conducted on 883 young people in order to know whether marketing efforts have led to the use of video games on Smartphone generating in them a possible addictive behavior. We found that men have more addictive than women and they are the most affected by marketing efforts made by companies to increase consumption of various products; in addition to the ones related to video games